Preventable Deaths Attributable to Second-Hand Smoke in Southeast Asia-Analysis of the Global Burden of Disease Study 2019 - Janni Leung; Carmen Lim; Tianze Sun; Giang Vu; Caitlin McClure-Thomas; Yangping Bao; Lucy Tran; Thomas Santo; Fitri Fausiah; Ghea Farassania; Gary Chung Kai Chan; Susy K. Sebayang (Frontiers Media S.A., 2024)
ObjectivesIn addition to harms caused to individuals who smoke, second-hand smoke (SHS or passive smoke) is an important public health issue. We aim to estimate the extent of preventable deaths due to tobacco and SHS exposure in Southeast Asia.MethodsData were from the Global Burden of Disease Study 2019. We analysed data from Southeast Asia, including Cambodia, Indonesia, Laos, Malaysia, Maldives, Mauritius, Myanmar, Philippines, Seychelles, Sri Lanka, Thailand, Timor-Leste, and Vietnam.ResultsIn 2019, there were 728,500 deaths attributable to tobacco in Southeast Asia, with 128,200 deaths attributed to SHS exposure. The leading causes of preventable deaths were ischemic heart disease, stroke, diabetes mellitus, lower respiratory infections, chronic obstructive pulmonary disease, tracheal, bronchus, and lung cancer. Among deaths attributable to tobacco, females had higher proportions of deaths attributable to SHS exposure than males in Southeast Asia.ConclusionThe burden of preventable deaths in a year due to SHS exposure in Southeast Asia is substantial. The implementation and enforcement of smoke-free policies should be prioritized to reduce the disease burden attributed to passive smoking in Southeast Asia.